2017
DOI: 10.1007/s11130-017-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Tef: The Rising Ancient Cereal: What do we know about its Nutritional and Health Benefits?

Abstract: This review covers the nutritional significance of tef cereal as compared to other common cereals with emphasis on carbohydrate content and starch digestibility, protein content, iron and zinc bioavailability and antioxidant potentials. Tef is a gluten free cereal and contains the highest iron and calcium among other cereals. It has high micro- and macro- nutritional profile and is becoming globally popular in the healthy grain food chain. Tef starch has a high gelatinization temperature, an essential precondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…The results showed significantly (p ≤ 0.05) higher total phenol content on tef flours (56.50–74.53 mg GAE/100 g) compared to rice flours (21.13 mg GAE/100 g). In addition, higher values were observed in white tef, compared to the brown, results in agreement with those found by other authors (Forsido et al., 2013; Salawu et al., 2014; Shumoy and Raes, 2017). These authors reported higher soluble phenolic content in white tef varieties, while brown varieties showed higher bound and total phenolic content.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The results showed significantly (p ≤ 0.05) higher total phenol content on tef flours (56.50–74.53 mg GAE/100 g) compared to rice flours (21.13 mg GAE/100 g). In addition, higher values were observed in white tef, compared to the brown, results in agreement with those found by other authors (Forsido et al., 2013; Salawu et al., 2014; Shumoy and Raes, 2017). These authors reported higher soluble phenolic content in white tef varieties, while brown varieties showed higher bound and total phenolic content.…”
Section: Resultssupporting
confidence: 93%
“…Other differences found are associated to the presence of apigenin glycosides in white tef, while luteolin glycosides are present in brown tef. Shumoy and Raes (2017) observed significant differences in the phenolic profiles of seven varieties studied, although some common characteristics were also reported, such as the important percentage of bound phenolic compounds (over 84%), or the lack of gallic, caffeic and salicylic acids. Its antioxidant properties contribute on the reduction of adipose tissue and inflammation processes among others (Lemecha et al., 2018).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Recently, teff has been recognized and is highly appreciated as a 'superfood' (Baye, 2015;Heuzé et al, 2016;Shumoy and Raes, 2017). It is relatively rich in protein, ranging from 8.4-19.4% of dry matter, depending on the cultivar, location, and year (CGIAR, 2009), but is gluten-free, and therefore considered an excellent solution for the increasing gluten-sensitive population worldwide (Baye, 2015).…”
Section: Introductionmentioning
confidence: 99%